2023
DOI: 10.3390/biomedicines11020507
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Graft Development Approaches for ACL Reconstruction or Regeneration

Abstract: The Anterior Cruciate Ligament (ACL) is one of the major knee ligaments, one which is greatly exposed to injuries. According to the British National Health Society, ACL tears represent around 40% of all knee injuries. The number of ACL injuries has increased rapidly over the past ten years, especially in people from 26–30 years of age. We present a brief background in currently used ACL treatment strategies with a description of surgical reconstruction techniques. According to the well-established method, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…The incidence of anterior cruciate ligament (ACL) injuries is increasing [1]. The gold standards for ACL reconstruction are autografts such as Hamstring muscle tendons and allografts [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of anterior cruciate ligament (ACL) injuries is increasing [1]. The gold standards for ACL reconstruction are autografts such as Hamstring muscle tendons and allografts [1].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of anterior cruciate ligament (ACL) injuries is increasing [1]. The gold standards for ACL reconstruction are autografts such as Hamstring muscle tendons and allografts [1]. Due to the limited availability of auto-and allografts as well as the donorside morbidity of autografts, a tissue-engineered alternative would be of high interest for surgeons [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, surgical techniques and graft choices have evolved considerably, offering a wider array of options to orthopedic surgeons and patients alike [ 3 , 4 ]. A successful ACLR heavily relies on optimal graft integration, which can be influenced by several factors, including the choice of autograft and other inherent biological considerations [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the risk of ACL injury is higher in competitive women and young athletes aged 15-25 years [5,6]. ACL is particularly important for people with high physical activity because it adjusts the stiffness of the quadriceps (Q) and hamstring (H) muscles, which form the agonist-antagonist structure of the knee [7]. Following ACL injuries, mechanical, proprioceptive, and efferent neuromuscular disorders, decreased muscle function and strength, and an imbalance in strength-torque generation may be observed [8,9].…”
Section: Introductionmentioning
confidence: 99%